Malaysia’s 15th General Election: ethnicity remains the key factor in voter preferences - Mohamad, Marzuki; Suffian, Ibrahim (ISEAS - Yusof Ishak Institute, 2023)
In Malaysia’s 15th General Election, no single coalition achieved a majority in the Dewan Rakyat. This paved the way for Pakatan Harapan (PH) to form a government with the other major coalitions, except the Perikatan Nasional (PN). This election reaffirmed that change of government in Malaysia is possible. The emergence of post-election political realignments comprising rival parties points to more vibrant democratic contestation taking place in a country where race has hitherto been the main barrier to changes of government. However, our study based on voter surveys and election results shows that ethnicity remains the key underlying factor determining voters’ political choices. Other variables such as economic concerns, governance issues and political stability are also at work, but are secondary to ethnicity. As secondary factors, these other variables come into play to determine voters’ choice within an ethnic group only when no single party commands majority support in that ethnic group. While Malaysia has shown impressive progress towards ending one-party dominance and has paved the way to more vibrant democratic contestation, one should not ignore race as an underlying factor which still determines voters’ political choices. Because the Malay votes were split (mainly between UMNO and PN, and with PH to a lesser degree), the post-election manoeuvrings and realignments led to a somewhat paradoxical situation where PH gained the right to lead the government even though its mainstay of support came from the non-Malay voters. This could imply that the current political configuration is intrinsically fragile, with the risk of being unravelled by further realignments among the Malay parties.